Preliminary identification and evaluation of parameters affecting the capacity of the operator-earthmoving machine system - Radziszewska-Zielina, Elżbieta; Sobotka, Anna; Plebankiewicz, Edyta; Zima, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Without reliable data on the time of work of construction machines it is impossible to calculate the cost of the investment or the time limit for its implementation. Machine capacity is affected by many factors resulting from both the technical capabilities of a machine (e.g. the engine and bucket capacity) and work environment (e.g. soil loosening and weather conditions). Capacity is also influenced by factors affecting the operator (e.g. health condition, stress, fatigue). Therefore, it is appropriate to use the concept of the operator-machine system. The current system for the standards of machine working time collected in catalogues of capital expenditures is outdated (a lack of modern materials, technology and equipment currently used). It does not take into account all possible weather conditions, labour conditions and soil and water conditions. The result of this state of affairs may be overestimation or underestimation of an investment. On the basis of the conducted research it may be concluded that the greatest impact on the capacity of the operator-earthmoving machine system is exerted by parameters associated with the psychophysical condition of the operator (experience, fatigue, health and motivation of the operator) and the technical parameters of the machine (technical condition and theoretical technical capacity). Weather conditions, particularly air humidity, affect the performance to the smallest extent.